2018
DOI: 10.3906/sag-1803-235
|View full text |Cite
|
Sign up to set email alerts
|

Value of shear wave elastography by virtual touch tissue imaging quantification in patients with diffuse thyroid gland pathology

Abstract: Background/aim: This study was performed to assess the diagnostic accuracy of shear wave elastography by virtual touch tissue imaging quantification in patients with diffuse thyroid gland pathology and to differentiate Graves' disease from Hashimoto's thyroiditis. Materials and methods: Thirty patients with Hashimoto's thyroiditis and 22 patients with Graves' disease were evaluated with conventional ultrasonography and shear wave elastography by virtual touch tissue imaging quantification. Thirty healthy parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…The mean SWE values ± SDs of patients with GD were found to be between 17.6 ± 6.4 and 27.05 ± 12.21 kPa 16,18 and between 2.61 ± 0.32 and 2.71 ± 0.22 m/s 20,21 in previous studies. The mean SWE values of control groups consisting of adult participants were found to be between 10.97 ± 3.1 and 14.3 ± 2.7 kPa 16–18 and between 1.63 ± 0.12 and 1.92 ± 0.14 m/s 8,20,21 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mean SWE values ± SDs of patients with GD were found to be between 17.6 ± 6.4 and 27.05 ± 12.21 kPa 16,18 and between 2.61 ± 0.32 and 2.71 ± 0.22 m/s 20,21 in previous studies. The mean SWE values of control groups consisting of adult participants were found to be between 10.97 ± 3.1 and 14.3 ± 2.7 kPa 16–18 and between 1.63 ± 0.12 and 1.92 ± 0.14 m/s 8,20,21 …”
Section: Discussionmentioning
confidence: 93%
“…In studies evaluating thyroid parenchyma using SWE, the quantitative elasticity values were measured only as kilopascals 16–18 or only as meters per second 8,19–21 . In a limited number of studies, the quantitative elasticity values were measured as both meters per second and kilopascals 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Sporea et al [25] compared the SWV among 29 patients with GD, 22 patients with CAT, and 23 control subjects and found a significantly higher SWV in the GD than in the CAT group (2.82 ± 0.47 vs. 2.49 ± 0.48 m/s, respectively). Furthermore, Rahatli et al [26] in a study included 30 patients with HT and 22 patients with GD found patients with GD had significantly higher shear wave velocities than those with HT ( P < 0.001). The difference between the results of current study and these two studies may be due to difference in number of the patients, and the fact that most of patients with HT included in the study was in chronic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the role of SWE in the thyroid disease have been focused on nodules so far. There is only a limited number of studies concerning SWE in diffuse thyroid disease [4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…List of publications comparing mean stiffnesses of normal thyroid and in diffuse thyroid disease[4][5][6][7][8][9][10][11][12] . DTD diffuse thyroid disease; N° number of healthy volunteers/number of patients, RL right lobe, LL left lobe; grey numbers are approximate values calculated with the formula Young's modulus…”
mentioning
confidence: 99%